2004
DOI: 10.1007/s00392-004-0157-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gender on treatment and short-term mortality of patients with acute myocardial infarction in Berlin

Abstract: Even after adjustment in multivariate analysis, women with acute myocardial infarction still demonstrate a higher risk for in-hospital death than men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 38 publications
1
9
0
1
Order By: Relevance
“…After adjustment, women without diabetes (OR = 0.99 with 95% CI 0.64-1.54) have the same risk of dying in hospital as their male counterparts. These results also signify that the higher hospital mortality of female AMI patients previously described by us 6 and by other authors 1,8,22 may be explained by the interaction among being simultaneously female and diabetic and aged ≤ 75 years.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…After adjustment, women without diabetes (OR = 0.99 with 95% CI 0.64-1.54) have the same risk of dying in hospital as their male counterparts. These results also signify that the higher hospital mortality of female AMI patients previously described by us 6 and by other authors 1,8,22 may be explained by the interaction among being simultaneously female and diabetic and aged ≤ 75 years.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, we found that women with AMI have a higher risk of in-hospital death than do men after adjustment in multivariate analysis. 6 …”
mentioning
confidence: 99%
“…Th e above given facts partially explain statistics registered worldwide [20][21][22][23][24][25][26][27][28] demonstrating that in the case of CVD emergency and compared to male CVD patients, women experience • later hospitalisation after symptom onset of acute CVD • longer period of time before the treatment initiation, if any provided • less likely intensive care settings • illegibility for usual therapies, due to co-morbid disorders more frequent in female CVD patients • less likely or delayed application of reperfusion therapy.…”
Section: Women Experience Delayed Care In the Case Of Cvd Emergency: mentioning
confidence: 89%
“…Th ey need to become integrated with what we already know. Based on updated meta-analyses with trial sequential analyses [22][23][24] in systematic reviews -taking both the risks of systematic errors [15,16] and risks of random errors [22][23][24] into account -we need to design new randomised trials in fi elds where the evidence is still not conclusive. In fi elds where the evidence is conclusive, the interventions have either to be implanted in clinical practice or research programmes redirected in case the intervention does not work or is causing more harm than benefi t. Such activities takes time, but due to the constant fl ow of new research fi ndings patients and relatives may rest assured that new preventive, diagnostic, prognostic, and therapeutic interventions are on their way.…”
Section: What Is a Realistic Timeline For The Incorporation Of Pppm Imentioning
confidence: 99%
“…1,6,12) No influence of gender on mortality was detected by our multivariate analysis, which correlates with other papers. 20,21) Some other studies reported female gender to be a firm risk factor of death 22,23) although studies conducted on larger cohorts and involving different populations should be compared carefully. The same multivariate analysis showed that dyslipidemia influences the risk of death by a decrease in its level.…”
Section: Discussionmentioning
confidence: 99%